CLCC1 promotes hepatic neutral lipid flux and nuclear pore complex assembly - Alyssa J. Mathiowetz; Emily S. Meymand; Güneş Parlakgül; Niek van Hilten; Emily F. Torres; Leonardo L. Artico; Kirandeep K. Deol; Mike Lange; Stephany P. Pang; Cody E. Doubravsky; Melissa A. Roberts; Danielle M. Jorgens; et al. (Nature, 2026)
Abstract Imbalances in lipid storage and secretion lead to hepatic steatosis, the accumulation of lipid droplets in hepatocytes 1,2 . Our understanding of the mechanisms that govern the channelling of neutral lipids in hepatocytes towards cytosolic lipid droplets or secreted lipoproteins remains incomplete 3,4 . Here we performed a series of CRISPR–Cas9 screens under different metabolic states that led to the identification of CLCC1 as a critical regulator of neutral lipid storage and secretion in hepatocytes. Loss of CLCC1 resulted in the buildup of large lipid droplets in hepatoma cells and Clcc1 knockout in mice caused liver steatosis. Lipid droplets were present in the lumen of the endoplasmic reticulum of the Clcc1 -knockout hepatocytes and exhibited properties of lipoproteins, indicating a profound shift in neutral lipid flux. The loss of CLCC1 also led to the accumulation of nuclear membrane herniations accompanied by a reduction in nuclear pores. Remote homology searches identified a domain in CLCC1 that is homologous to yeast Brl1 and Brr6, factors that promote nuclear envelope fusion during nuclear pore complex assembly. Molecular dynamics simulations and mutagenesis studies support a model in which CLCC1 mediates membrane bending and fusion. We propose that CLCC1 mediates membrane fusion to promote hepatic neutral lipid flux and nuclear pore complex assembly.